2011
DOI: 10.1007/s10815-011-9611-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sperm chromatin condensation and ploidy status using flow cytometry correlates to fertilization, embryo quality and pregnancy following in vitro fertilization

Abstract: Purpose Sperm flow cytometry (SFC) was used to evaluate the association of sperm chromatin condensation and ploidy with fertilization, embryo development, pregnancy and abortion rates following IVF. Methods Conventional semen analysis was performed in one hundred fifty men, as well as SFC analysis, after acridine orange and propidium iodide staining, for the evaluation of sperm maturity and ploidy respectively. Conventional IVF was performed in all couples. Results Couples with low percentages of mature sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
2
17
0
2
Order By: Relevance
“…We noted also that the degree of sperm chromatin compaction was significantly correlated with the average number of sperm head abnormalities and the acrosome abnormalities. These results confirm earlier investigations [12, 19, 24, 28–30] that demonstrated significant correlations between sperm morphology and its nuclear condensation. Similarly, Kazerooni et al [17] showed a significantly higher percentage of AB-positive spermatozoa among men with teratozoospermia when compared with normozoospermic group (31.6% versus 14.1%; P < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…We noted also that the degree of sperm chromatin compaction was significantly correlated with the average number of sperm head abnormalities and the acrosome abnormalities. These results confirm earlier investigations [12, 19, 24, 28–30] that demonstrated significant correlations between sperm morphology and its nuclear condensation. Similarly, Kazerooni et al [17] showed a significantly higher percentage of AB-positive spermatozoa among men with teratozoospermia when compared with normozoospermic group (31.6% versus 14.1%; P < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Probably, the presence of high percentages of histone in morphologically normal spermatozoa can be a sign of defective genome silencing and faulty imprinting pattern. Studies on condensation anomalies correlating ART outcome revealed that protamine deficiency negatively affects both fertilization rate and pronuclear morphology (Nasr-Esfahani et al, 2006;Lazaros et al, 2011). In the present study, normal spermatozoa with condensation defects had a negative effect on fertilization rate in IVF; that was supported by another study where risk of fertilization failure was higher in the samples with increased percentages of abnormal spermatozoa and condensation defects (Esterhuizen et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…With respect to sperm parameters, properly condensed sperm nucleus is essential to undergo decondensation for pronucleus formation during fertilization (Tosti & Fortunato, 2011). Declined rate of fertilization, embryo quality, and pregnancy outcome were also recorded in semen samples with aneuploid and immatured spermatozoa (Lazaros et al, 2011). Moreover, higher prevalence of abnormal chromatin condensation was marked in teratozoospermia cases Utsuno et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuorescence microscopy of samples stained with acridine orange, aniline blue and toluidine blue, acridine orange-propidium iodide is used for identification of sperm nuclei with the abnormal chromatin condensation and the ploidy (Erenpreiss et al 2001, Erenpreisa et al 2002, Bungum et al 2007, Mahfouz et al 2009, Moskovtsev et al 2009, Lazaros et al 2011, Montjean et al 2012.…”
Section: Evaluation Of Sperm Morphologymentioning
confidence: 99%